From Paris to Pompeii : French Romanticism and the Cultural Politics of Archaeology - Blix, Göran Magnus, 1971- (Book collections on Project MUSE., 2009)
"From Paris to Pompeii reveals how the nascent science of archaeology lay at the core of the romantic experience of history and shaped the way historians, novelists, artists, and the public at large sought to cope with the relentless change that relegated every new present to history." "In postrevolutionary France, the widespread desire to claim that no being, city, culture, or language was ever definitively erased ran much deeper than mere nostalgic and reactionary impulses, Goran Blix contends that this desire was the cornerstone of the substitution of a weak secular form of immortality for the lost certainties of the Christian afterlife. Taking the iconic city of Pompeii as its central example. and ranging widely across French romantic culture, this book examines the formation of a modern archaeological gaze and analyzes its historical ontology, rhetoric of retrieval, and secular theology of memory, before turning to its broader political implications."--Jacket.